Determinants Of Budgetary Slack: The Influence Of Budget Preparer Behaviour In Local Government : Faktor Penentu Senjangan Anggaran: Pengaruh Perilaku Penyusun Anggaran Di Pemerintah Daerah - Lhutfi, Iqbal (Jurnal Pendidikan Akuntansi Indonesia, 2025)
This study aims to examine the influence of budget preparers’ behaviour on budgetary slack within the local government context, specifically in the Pariaman City Government. Employing a quantitative approach, primary data were collected through questionnaires distributed to 34 respondents, including heads and staff of regional apparatus organisations (OPD) involved in the budgeting process for at least three consecutive years. The study applies simple linear regression analysis to assess the relationship between the behaviour of budget preparers and the occurrence of budgetary slack. The results demonstrate that budget preparers’ behaviour has a significant positive effect on budgetary slack (p < 0.05; R² = 0.135), indicating that individual characteristics and values play a crucial role in shaping budget-related outcomes. The findings highlight the importance of understanding personality-driven behaviours in enhancing budget transparency and accountability in public sector organisations. This research contributes to the literature by providing empirical evidence on the behavioural determinants of budgetary slack in Indonesian local governments, and offers practical implications for policymakers to design interventions that foster ethical behaviour and reduce slack in the budgeting process. Limitations and directions for future research are also discussed.